(untitled) (Karapan Network Journal : Journal Computer Technology and Mobile Ad Hoc Network, 2025)
Water quality is an important aspect in the success of pond aquaculture, especially temperature and clarity parameters that directly affect the physiological conditions of farmed organisms. Manual water quality monitoring has limitations in terms of continuity and speed of data access. This study aims to develop an Internet of Things (IoT)-based telemetry system as a solution for real-time and remote monitoring of pond water parameters. The system is designed using temperature and turbidity sensors integrated with a microcontroller and a wireless communication module for data transmission to an internet-based server. The measurement data is displayed through a web-based monitoring platform so that it can be accessed by users at any time. The research methods included hardware design, software development, and system performance evaluation. The test results showed that the system was capable of measuring water parameters with a good level of accuracy and stable data transmission. The developed system can provide continuous information on water quality conditions and support faster and more accurate decision-making in pond management. Thus, this IoT-based telemetry system has the potential to increase the efficiency and productivity of pond aquaculture.